Penerapan Embedded System pada Sistem Pintar Pengendali Multi Perangkat dalam Kelas berbasis Intel Galileo dan Web - Silfia Rifka; Firdaus Firdaus; Waldito Febri Ramadhan (Jurnal Rekayasa Elektrika, 2018)
Smart systems are widely used in smart building, smart home, smart car, smart class, and others. The smart system in this paper is the result of research, exploit module microcontroller Intel Galileo technology and the Internet of Things (IoT) as a controller, which controlled devices connected to the system remote control from a web-based accessible via smart devices (smartphones, tablets, and laptops). Intel Galileo is a microcontroller module that combines a mini computer and Arduino is open source and supports IOT technology and the web. Web selection as a remote control in this research to facilitate system users to be able to control the system remotely by using the existing browsers on smart devices although the operating system is different. The devices controlled in this system are the LED (on-off automatically and setting the intensity of light), air conditioning (on-off automatically, temperature settings), a projector (on-off), and the IP camera (moved up, down, left and right) to monitor the room. All controlled embedded devices to facilitate the control and effective use of smart controllers resulting in a centralized system for multi-devices in the classroom to realize the smart class.